F37. EXAMINATION OF SOCIAL DECISION MAKING IN PATIENTS WITH SCHIZOPHRENIA USING ULTIMATUM GAME. (9th April 2019) - Patil, Vaishnavi; Jacob, Arpitha; Thonse, Umesh; Devi, Priyanka; Shah, Aishwarya; Kumar, Vijay; Varambally, Shivarama; Venkatasubramanian, Ganesan; Rao, Naren
Abstract: Background: Decision making in a social situation is an essential aspect for optimal societal functioning. Despite its importance, only a few studies have examined social decision making in schizophrenia (SCZ), a disorder with impairments in several sub-domains of social cognition. One important reason is the difficulty in examining social decision making in lab setting due to its interactive nature. Neuroeconomic paradigms permit simulation of social interaction in a lab setting. In this study we examined social decision making in SCZ using a valid neuroeconomic paradigm, Ultimatum Game (UG) in comparison with healthy volunteers (HV). Methods: Thirty male patients with Structured Clinical Interview for DSM-IV (SCID-I) diagnosed SCZ (age=30 + 7.08 years) and thirty male HV (age=28.48 + 3.73 years) participated in the study. Clinical severity was assessed using Positive and Negative Syndrome Scale, Scale for the Assessment of Negative Symptoms, and Calgary Depression Rating Scale. Participants played a previously validated version of Ultimatum game (Güth, W. et.al. J. Econ. Behav. Organ. (1982)) Participants played the role of a responder and had to either accept or reject offers made by an anonymous proposer for sum of money Rs.10/- in each trial. In each trial, one of the six split possibilities (proposer: responder - 9:1, 8:2, 7:3, 6:4, 5:5, 4:6) were offered as split. A total of 48 trials were played with each split played 8 times. The order of splits was randomized. For analysis, the offers were grouped into fair offers (6:4, 5:5, 4:6) or unfair offers (9:1, 8:2, 7:3) as per the previous studies. Data was analyzed using SPSS v 24. Since the data was not normally distributed, Mann-Whitney test was used to examine group differences. Results: The groups were matched in age (p=0.48). SCZ had significantly lower acceptance rates for fair offers (median=15.00, range = 13.75 to 16.00) compared to HV (median =16, range = 15 to 16) (U= 311.50; p=0.02). However, there was no significant difference between SCZ (median =13.50, range = 4.00 to 19.75) and HV (median = 11.50, range =6.50 to 26.25) for unfair offers (U= 431.50; p= 0.78). When individual offers were analyzed, lower acceptance rate for 6:4 split was significantly higher (U=291; p=0.01) in SCZ (median =4.00, range =3.00 to 7.00) compared to HV (median =8.00, range =4.75 to 8.00) but not for 5:5 (U=344; p=0.06) or 4:6 (U=349.50; p=0.07). There was no significant correlation between rejection rates and clinical severity scores on PANSS, SANS or CDS. Discussion: The results of the study suggest significantly higher rate of lower acceptance in SCZ for slightly unequal offers. While healthy volunteers refused unfair offers but accepted slightly unequal offers as fair, SCZ refused these offers. This indicates SCZ may have a higher threshold to accept division as fair as there was no significant difference when the split was equal or favorable to respondent. Whether these deficits are primary or secondary to deficits in other domains of social cognition, like theory of mind, need to be examined in the future. Considering the importance of economic interactions and social decision making in recovery, findings of the study could have implication in rehabilitation and functional recovery.